Navigating Capital Structures Through ESG and Gender Diversity: Evidence from ASEAN Countries - Rifiana, Alya Syafi; Rokhim, Rofikoh (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The integration of Environmental, Social, and Governance (ESG) criteria into corporate strategies has gained prominence as companies aim to improve transparency, reduce capital costs, and meet stakeholder expectations. Simultaneously, board gender diversity has been recognized as a critical factor influencing corporate governance and financial decision-making. This study aims to examine and analyze the influence of ESG performance and board gender diversity on capital structure. This research was conducted in 5 ASEAN countries, using the Random Effect Model static panel regression test and a research period of 6 years, from 2018 to 2023. The results showed that ESG performance negatively affects the capital structure as measured by book leverage. Meanwhile, gender diversity shows a positive effect on capital structure as measured by book leverage. This finding aligns with Stakeholder Theory, which posits that ESG engagement builds investor trust, leading to a preference for equity financing.